Martial power and Elizabethan political culture: military men in England and Ireland, 1558 - 1594 - Rapple, Rory (Cambridge studies in early modern British history, 2009)
Chimneys in summer -- Martial men and their discontents -- The limits of allegiance : English martial men, Europe and the Elizabethan regime -- The captains and the Irish context -- The limits of imperium : martial men and government -- The limits of rhetoric : the captains and violence in Elizabethan Ireland to 1588 -- Unlimited indemnity : delegates versus viceroys